Mental training driven by a winning mindset in the Chinese national ice hockey team: implications of medal-winning practices for the youth Ice hockey training system - Sun, Z.; Song, Z.; Hu, Y.; Gao, R.; Guo, Y.; Sun, X.; Wang, L.; Hu, Y.; Zhang, M.; Zhang, N. (Frontiers in Sports and Active Living, 2026)
Background: Based on Miller's psychological model of ice hockey success, this study aims to develop a specialized and systematic mental training program for Chinese female 3v3 ice hockey athletes, providing empirical evidence for improving the competitive performance of China's ice hockey teams and the psychological development of reserve talents.